Traditional Meat and Fish Preservation Practised by the Mising Community - Borthakur, Mridusmita; Borthakur, Sanjoy; Saud, Ranjit Kumar; Neog, Manoranjan (International Journal of Bio-resource and Stress Management, 2026)
The present study was conducted from April, 2023 to March, 2024 in the Golaghat district of Assam, India to document and scientifically validate the traditional meat and fish preservation techniques practiced by the Mising community. These indigenous practices, primarily drying, smoking, and salting, had been developed through generations as adaptive strategies to local ecological conditions and play an important role in ensuring food availability, cultural continuity, and nutritional security among tribal households. Traditionally processed fish and meat samples were collected and subjected to biochemical analysis using standard analytical procedures. Proximate composition parameters, including moisture, ash, fat, fibre, protein, and carbohydrate content, along with mineral composition such as calcium and iron, were analyzed to assess their nutritional quality. Results indicated that dried fish contained 63.57 g 100 g-1 of protein, 37.30 mg 100 g-1 of iron, and 415.45 mg 100 g-1 of calcium. Meat samples recorded 54.53 g 100 g-1 protein, 19.10 g 100 g-1 ash, 18.15 g 100 g-1 fat, and 411.40 mg 100 g-1 calcium. The findings demonstrated that traditionally processed fish and meat products served as significant dietary sources of protein and minerals with potential relevance for addressing nutritional deficiencies, including iron-deficiency anaemia, which remains a serious public health issue among women in Assam. The work also underscored the significance of preserving indigenous knowledge systems, as these traditions represent sustainable, low-cost, and environmentally aligned practices. The integration of such ancestral knowledge into contemporary nutrition and public health strategies could contribute to improve dietary security and cultural preservation in rural tribal communities.